An evaluative study of vocal hygiene awareness program in professional voice users (Prospective Teachers) - Rajasudhakar R; Pramoda K; Yeshoda K; Geetha YV (Journal of All India Institute of Speech and Hearing, 2011)
Vocal hygiene education program addresses the importance of proper care of vocal fold tissue suggesting certain changes in behaviors, patterns, life style and diet. It is an effective method to create awareness, reduce vocal abuse and prevent onset and progression of voice problems among the teachers and other professional voice users. The effectiveness of such sensitization programs has not been documented in the Indian context. The present study aimed to evaluate the short-term effect of a vocal hygiene awareness program among the teacher training students in Mysore city. The program consisted of three consecutive sessions on anatomy of voice production, causes of voice disorders and vocal hygiene tips to teachers, delivered audio-visually by experienced speech language pathologists. A basic questionnaire consisting of 10 questions (one open ended and nine close ended) was prepared, which was divided into three sections based on different areas of voice. The questionnaire was administered prior to and after the sensitization program. The efficacy was determined based on participant’s ability to answer the questions. The results showed that the average percent scores improved from 58% (pre-test) to 73% (post-test) after attending the program. Further studies that address other voice care domains in the questionnaire like vocal and non-vocal practices, diet, and classroom management and the long-term effect of such programs have to be addressed to understand the effectiveness of such programs.